Frozen embryo transfer at the cleavage stage can be performed within the first menstrual cycle following the freeze-all strategy without adversely affecting the live birth rate: A STROBE-compliant retrospective study. Issue 38 (September 2019) - Song, Jingyan; Xiang, Shan; Sun, Zhengao
Abstract : Abstract: Thus far, all clinical trials evaluating the efficacy of embryo transfer strategies have selectively delayed the first frozen embryo transfer (FET) by at least 1 menstrual cycle. Nevertheless, this approach, which is based solely on clinical experience, may create unnecessary psychological stress on infertile patients who are anxious to conceive as soon as possible. This study aimed to investigate whether the time interval between oocyte retrieval and subsequent FET affects reproductive outcomes. We implemented a large retrospective cohort study in a single assisted reproductive technology (ART) unit at a university-based hospital, including 1540 autologous FET cycles performed in freeze-all cycles. The beginning of the FET was classified as either 'cycle 1' (performing FET within the first menstrual cycle) or 'cycle ≥2' (performing FET after one or more menstrual cycles). Live birth rate (LBR) was the primary outcome of our study. The mean interval for 'cycle 1' and 'cycle ≥2' FETs was 25.72 ± 5.10 days and 75.33 ± 24.85 days, respectively ( P  < .001). The type of controlled ovarian hyperstimulation (COH) and endometrial preparation protocols differed significantly between groups ( P  = .008 and P  = .004, respectively). However, FET groups were similar in many ways. Univariate analysis showed that there was no significant difference in LBR between the different cycles (33.1% after 'cycle 1' FET vs 34.2% after 'cycle ≥2' FET, P  = .68). To evaluate whether LBR remained unchanged after adjustment for potential confounders, we performed multivariate logistic regression. FET timing had no significant impact on LBR in the first FET (odds ratio [OR]: 1.06, 95% confidence interval [CI]: 0.80–1.39). In accordance with the present study, it might not be necessary for clinicians to wait more than 1 menstrual cycle before performing FET. This allows us to reduce otiose deferment in FET, without adversely affecting reproductive outcomes.